Who will use electric vehicles? - Elisabeth Dütschke; Uta Schneider; Anja Peters (Fraunhofer-Institut für System- und Innovationsforschung ISI, 2013)
Electric vehicles (EVs) are currently seen as an important means to make transport more sustainable; however, so far, only a few EVs are actually on the roads. This paper tries to identify likely early private users of EVs based on a narrative review of results from earlier studies by the authors. Two usage scenarios are analyzed: (1) the traditional model of car use where the EV is bought or leased by the household whose members drive the vehicle (individual usage), and (2) concepts where EVs are used as part of shared fleets (collective usage). Findings indicate that, for both scenarios, likely early users are highly educated middle-aged men. Those who live with their family in rural or suburban regions seem to be more interested in owning an EV; for those living in urban areas, carsharing might be an attractive alternative. Other likely user groups are also discussed in the paper.
urn:nbn:de:0011-n-2596916
Keywords: 330